Judging state-sponsored violence, imagining political change - Leebaw, Bronwyn Anne (Cambridge University Press, 2011)
"This book offers a new way to think about the legacies of the Nuremberg Trials and South Africa's Truth and Reconciliation Commission, which transformed the theory and practice of transitional justice"--